Preparation of Na2Ti3O7/Titanium Peroxide Composites and Their Adsorption Property on Cationic Dyes - Meixia Zhao; Jiguo Huang; Xueting Guo; Haitao Chen; Hai Zhao; Lili Dong; Xing-juan Liu (Journal of Chemistry)
Na2Ti3O7/titanium peroxide composites (TN-TP) were successfully prepared with the reaction of Ti foils, NaOH, and H2O2 at 60°C for 24 h in water bath. The Na2Ti3O7 appeared as nanorods in composites. Water bath temperature, water bath time, and the concentration of H2O2 and NaOH were crucial. The reaction mechanism was proposed. TN-TP was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and thermogravimetric and differential scanning calorimetry (TG-DSC). TN-TP was a mesoporous material and exhibited stronger adsorption capability for neutral red (NR), malachite green (MG), methylene blue (MB), and crystal violet (CV) than pure Na2Ti3O7 and pure titanium peroxide, and the saturated adsorption capacities were 490.21, 386.13, 322.81, and 292.74 mg/g at 25°C, respectively. It was found that the pseudo-second-order kinetic model and the Langmuir model could well describe the adsorption kinetic and isotherm of cationic dyes studied. The results of this work are of great significance for environmental applications of TN-TP as a promising adsorbent material for dyeing water purification.